Dinâmica do efluxo de CO2 e da decomposição de resíduos afetada pelo tipo de cultura de cobertura e sistema de preparo - Keller, Cristiano (2015)
The liquid carbon accounting balance in the soil is important to identify agricultural practices that contribute to mitigation of global climate change. In this sense, research must be conducted to improve the accuracy of estimates of emission rates and C sequestration in field experiments to quantify the actual capacity of the soil to accumulate C and how much can be reissued to the atmosphere as CO2 by changes in soil management. This work is divided into two chapters, aims to investigate the relationship between tillage systems and types of wastes in emissions of C-CO2 and C sequestration potential. The study was conducted in plots making up the experiment "Influence of tillage and crop rotation on yield and profitability of crops", installed in 1985, located in the current Central Cooperative Gaucha LTDA Technology (CCGL-tec) former Foundation Experimentation and Research Center Fecotrigo (FUNDACEP), in Cruz Alta - RS. The first study evaluated the flow of C-CO2 for 125 days from November 2013 to March 2015, using dynamic closed flow chamber with infrared analyzer (LI-8100), combining tillage and conventional tillage (PC) reduced tillage (PR) and no tillage (NT) with different types of land cover. In the second combined if the cumulative flows of C-CO2 that period with the decomposition of crop residues of oat (Avena strigosa Schreber), common vetch (Vicia sativa (L.) Walp.) and the consortium of the same. The results indicated that in clayey Oxisol, in the absence of plant residues, the breakdown of households by tillage in PR and PC had limited increase in outflows of C-CO2. Soil moisture was the variable that best explains the variations of C-CO2 efflux for PR and NT cropping systems. The decay of outflows until reaching the lower phase and stable efflux differ among tillage systems, persisting in the PC until the end of the first month in PR until about 20 days after preparation and NT up to 7 days after sowing. Of the C-CO2 emissions from waste, the first 10 days after soil management were responsible for issuing the largest amount, especially in the PC ER waste with 445.0 kg ha-1 (19.4%) in PR AV+ER waste with 889.9 kg ha-1 (29.6%) and NT the ER waste with 384.9 kg ha-1 (24.5%). The type of coverage has an effect on the flow of C-CO2, with an increase of them as decreased the C/N waste to the PC and PR. In NT the portion with waste ER smaller C/N, was not significantly different PC and PR higher C/N, being less sensitive to variations of the C/N ratios. The time in which the soil acts as a sink for C-CO2 PC was 43, 40 and 10 days for waste AV, AV+ER and ER, respectively, from these periods the soil began to act as a source of C-CO2 into the atmosphere. In NT the influx of C-CO2 into the AV persisted until the end of the experiment, AV+ER and ER to the first 86 and 44 days respectively. Independent crop residue NT partial balance of C-CO2 in the soil was positive, with greater influx to the waste of AV, intermediate for the AV+ER consortium and less to the ER, with C the conversion rates of 24.8, 13.9 and 11.4% for waste AV, AV+ER and ER, respectively. In PC soil acts as C drain only when submitted to management with AV C with the conversion rate of 16.4%, in other managements soil served as a source of C-CO2 into the atmosphere with 103.7 and efflux 105.5% relative to the total C added to the residue consortium AV+ER and ER, respectively.